Modified Sampling Methodology for Estimation of Area and Production of Horticultural Crops - Tauqueer Ahmad; Prachi Misra Sahoo; Ankur Biswas; Kaustav Aditya; Deepak Singh; Raju Kumar (Journal of the Indian Society of Agricultural Statistics, 2026)
Reliable estimation of horticultural crop area and production is crucial for agricultural planning in India. The earlier Crop Estimation Survey-Fruits & Vegetables (CES-F&V) methodology developed by ICAR–IASRI was discontinued due to operational complexity and high cost, necessitating an alternative approach. This study presents a modified sampling methodology developed under the CHAMAN programme for integrated assessment of fruits and vegetables. Field testing across Maharashtra, Andhra Pradesh, Tamil Nadu, and Himachal Pradesh generated district-level estimates of area, production, and yield. The results showed close agreement with official statistics of the Department of Agriculture & Farmers Welfare, with acceptable precision levels. A significant reduction in sample size, from 150–200 to 80 villages per district, improved cost-effectiveness and operational efficiency without compromising accuracy. The methodology demonstrates strong potential for large-scale implementation, including the use of model-based approaches in low-productivity districts.